2021
DOI: 10.1093/ehjcr/ytab214
|View full text |Cite|
|
Sign up to set email alerts
|

Different reverse remodelling between left ventricle and right ventricle in fulminant heart failure due to giant cell myocarditis: a case report

Abstract: Background Giant cell myocarditis (GCM) is a rare cause of fulminant heart failure (HF). The most common presentation is progressive hemodynamic deterioration, and a few cases present with idiopathic complete atrioventricular block (cAVB). The prognosis of GCM is poor, and GCM patients usually die of HF and ventricular arrhythmia unless cardiac transplantation is performed. Few reports have described the effects of treatments such as immunosuppression and detailed reverse remodelling in GCM p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Generally, because of the complex anatomy of the RV, precise function assessment is difficult. Moreover, recent case reports have shown that in fulminant heart failure due to GCM, the pattern of reverse remodelling may be different between LV and RV ( 12 ). Prednisolone and cylosporin treatment resulted in the RV function recovery and improvement of heart failure symptoms, while the LVEF did not recover.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, because of the complex anatomy of the RV, precise function assessment is difficult. Moreover, recent case reports have shown that in fulminant heart failure due to GCM, the pattern of reverse remodelling may be different between LV and RV ( 12 ). Prednisolone and cylosporin treatment resulted in the RV function recovery and improvement of heart failure symptoms, while the LVEF did not recover.…”
Section: Discussionmentioning
confidence: 99%